The Genus Echinops: Phytochemistry and Biological Activities: A Review - Bitew, Helen; Hymete, Ariaya (Frontiers in Pharmacology, 2019)
The genus Echinops belongs to the family of Asteraceae and comprises about 130 spices. Many species belonging to the genus Echinops are traditionally used as medicinals mainly in Africa and Asia. The genus is reported to contain diverse secondary metabolites. The aim of this review is to critically evaluate the available research reports on the genus and systematically organize the findings. Information for this study was obtained using various search engines including PubMed and Google Scholar. This review revealed that the genus is used traditionally to treat pain, inflammation, respiratory diseases, diseases caused by different microorganisms, as an aphrodisiac, to fasten expulsion of placenta, and for removal of renal stones. More than 151 secondary metabolites have been reported from the genus in which thiophenic compounds held the biggest share. Various extracts, essential oils and isolated compounds from members of this genus are shown to exhibit different biological effects mainly anti-microbial, anti-proliferative, and anti-inflammatory. However, there are a number of species in this genus that are claimed to have traditional medicinal uses but their biological effect not yet been evaluated. .